US}U>L FIQH DAN QAWA>’ID AL-FIQHIYAH DALAM PRINSIP-PRINSIP EKONOMI ISLAM - Fageh, Achmad (Irtifaq, 2014)
Assessing and find a legal shari‟ah on contemporary issues (including economic activity) it is absolutely needed us}u>l fiqh. Supposing, fiqh is a production process to produce a product with the jurisprudence through operational standards qawa>‟id fiqhiyyah & us}u>l fiqh. Not qawa>‟id fiqhiyyah can accommodate the interests in the activities mu‟a>malah instead. Only a few of qawa>‟id was associated with the transaction qa‟i>dah instead. Thus, as a completely transaction grow and needs, it will require assessment more qa‟i>dah, with reference to the methods outlined in us}u>l fiqh. Key Word: Us}u>l fiqh, qawa>‟id fiqhiyyah and principle of Islamic economic